Konflik Pemisahan Daerah Karena Sumber Daya Alam (Studi Kasus Desentralisasi Bangka Belitung dan Rencana Desentralisasi Sulawesi Timur) - Zarina, Berlian; Muliasari MS, Nur; Indah Dalilah, Nurul; Meisawitri, Vania (Journal of Governance Innovation, 2024)
Natural resources that have commodity value in a region are increasingly contested, either by the parent region or the region as the autonomous owner of the resources concerned. The upheaval between regions is getting stronger when natural resources are considered to provide significant benefits, but are not directly proportional to the development of the region where the resources are located. This study examines the potential impacts of forming a new province in East Sulawesi, Indonesia. The region's abundant natural resources, particularly nickel, have attracted significant investment but also led to social and environmental challenges. The formation of a new province could exacerbate these issues if not carefully managed. Drawing on the experiences of Bangka Belitung, the study emphasizes the importance of good governance and equitable resource distribution. A constructivist risk analysis framework is proposed to address the complex interplay of factors influencing the region's development. Key recommendations include strengthening local governance, promoting community participation, and diversifying the economy to reduce reliance on natural resources. By carefully considering these factors, the formation of East Sulawesi can be an opportunity for sustainable development and improved quality of life for its residents.